PERBEDAAN EFEKTIVITAS PEMBERIAN PISANG RAJA DAN PISANG AMBON TERHADAP INDEKS KELELAHAN OTOT ANAEROBIK PADA REMAJA DI SEKOLAH SEPAK BOLA - Lone, Vicka Frantya; Ardiaria, Martha; Nissa, Choirun (Departemen Ilmu Gizi, Fakultas Kedokteran, Universitas Diponegoro, 2017)
Background : Anaerobic muscle fatigue occurs due to accumulation of lactic acid, causing soreness and reduced muscle contraction. Raja banana (Musa paradisiaca var. Sapientum L.) and Ambon banana (Musa paradisiaca var. Sapientum (L.) Kunt.) are high in carbohydrate and potassium which are involved in increasing blood glucose, thus consuming bananas before exercising may help prevent muscle fatigue.This study aimed to determine the effectiveness of Raja and Ambon bananas on anaerobic. muscle fatigue index of adolescents in football school.Methods :This study was a quasi-experimentusingthe posttest-only with control group design.Thirty-nine male adolescents aged 15-18 years at Terang Bangsa and Satria Kencana Serasi football schools were recruited and classified into 3 groups: control (240 ml of mineral water), group I (150 g Raja banana fruit), and group II (150 g of Ambon banana fruit). Anaerobic muscle fatigue was measured by Running-base Anaerobic Sprint Test (RAST) to calculate Anaerobic Fatigue (AF) value. Data were analyzed by One way ANOVA and ANCOVA test.Results :The average AF index in control group (11.53±2.20) was significantly different with group I (4.30±0.80; p=0.001), and group I with group II (9.76 ± 2.34; p=0,001). However not significantly different between the averageAF Index of control group withgroup II.Conclusion :There is a significant difference in the effectiveness of Raja and Ambon banana on reducing anaerobic muscle fatigue for adolescents in football school. Raja banana demonstratedbetter effects on muscle fatiguein comparison withAmbon banana.